Mona Lisa: sentidos múltiplos de um sorriso enigmático - Moraes, Érika de [UNESP] (FapUNIFESP (SciELO), 2013)
This article reviews the history of the famous painting by Leonardo da Vinci, the Mona Lisa or Gioconda, sixteenth century, aiming to discuss about some of the multiple senses (or discourses) around its meaning, with the support of the French branch of the Discourse Analysis, especially based on concepts developed by D. Maingueneau. As it is characteristic of the work of art, the senses are open, which does not exclude the possibility of detachment, among which we accentuated the "Mona Lisa smile" as one of the main traits of the authorship by Leonardo Da Vinci and, simultaneously, a trait propitious to aphorisation. Thus, the work of art is releasing of the exclusive authorship of Da Vinci and it suscitates several rereadings, which help composing a discursive ethos around this consecrated painting and, at the same time, which make circulating distinct stereotypes.

Este texto resgata um pouco da história da famosa pintura de Leonardo da Vinci, a Mona Lisa, ou Gioconda, do século XVI, com objetivo de discorrer a respeito de alguns dos múltiplos sentidos (ou discursos) em torno de seu significado, tendo como suporte o respaldo teórico-metodológico da Análise do Discurso de linha francesa, com base especialmente em conceitos desenvolvidos por D. Maingueneau.
Mona Lisa: multiple meanings of an enigmatic smile
Keywords: Mona Lisa; Discursive ethos; Aphorisation; Autorship; Mona Lisa; Ethos discursivo; Aforização; Autoria